Хоры: без сопровождения (В. Шебалин ; составитель А. Шебалина) - Шебалин Виссарион Яковлевич (1967)
Экземпляры: ИСК (20150330) / Инвентарный номер: н11429 / Цена: 0.80 / Сис.шифр: 85.941(2) / Авт.знак: Ш 36 / ББК: 85.941(2)